QUEUE SYSTEM ANALYSIS IN SERVICE OPTIMIZATION IN PT. BANK SULSELBAR MAIN BRANCH MAKASSAR CITY - Lamatinulu Ahmad; Windayani windayani; Muhammad Dahlan; Ahmad Padhil; Nurhayati Rauf (Center for Study and Journal Management FTI UMI, 2023)
PT. Bank Sulselbar is a regionally owned business entity engaged in banking services. Companies in the service sector must be able to provide the best service to meet the wishes of customers who require fast service. As the number of customers increases, there are queuing problems in serving customers, this problem results in many customers waiting for quite a long time. For this reason, this study aims to reduce the length of time waiting for customers to avoid queues that are too long . This research uses queuing theory analysis method with queuing model (M/M/S). The results of this study using queuing theory analysis, namely the model calculation (M/M/S) shows that the busy period occurs in the period 08.00-09.00, and 13.00-14.00 by adding 1 service facility from 6 to 7 customer service, there will be a decrease customer waiting time. The waiting time in the system in the time period of 08.00-09.00 from 25.15 minutes to 10.07 minutes, and the time period of 13.00-14.00 from 19.39 to 9.13 minutes